2000
DOI: 10.1016/s1010-7940(00)00540-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating donor-specific cytotoxic T lymphocytes with high avidity for donor human leukocyte antigens in pediatric and adult cardiac allograft valved conduit recipients✩

Abstract: Objective: Speci®c immunological responses may be involved in the process of cryopreserved allograft valved conduit (AVC) degeneration, which is more frequently seen in young recipients. Rejection of heart and corneal allografts is preceded by an increase in the fraction of cytotoxic T lymphocytes (CTL) with high avidity for donor human leukocyte antigens (HLA) circulating in both peripheral blood and the affected graft. These donor-speci®c high-avidity CTLs are regarded as the destructive cells capable of cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Although we did not specifically investigate the subclasses of CD8 + circulating cells, this observation appears particularly relevant in the view of homograft transplantation of the DE/CR tissue. In fact, GA-fixed pericardial implants are known to cause an increase of circulating cytotoxic [18] or helper [19] T cells and production of anti HLA-I antibodies, which correlate with graft failure [17]. Thus, the fixative-free decellularization/cryopreservation method used in the present study may be helpful to reduce the inflammatory and cell-mediated immune response in recipients, improving the long-term durability of the implants.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although we did not specifically investigate the subclasses of CD8 + circulating cells, this observation appears particularly relevant in the view of homograft transplantation of the DE/CR tissue. In fact, GA-fixed pericardial implants are known to cause an increase of circulating cytotoxic [18] or helper [19] T cells and production of anti HLA-I antibodies, which correlate with graft failure [17]. Thus, the fixative-free decellularization/cryopreservation method used in the present study may be helpful to reduce the inflammatory and cell-mediated immune response in recipients, improving the long-term durability of the implants.…”
Section: Discussionmentioning
confidence: 84%
“…We and others have found that patients receiving allograft valve transplantation show increased serum levels of anti HLA-1 antibodies [17] and of circulating cytotoxic and helper T-lymphocytes (CTLs, HTLs) [18], [19].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also correlated HLA mismatch with increased rate of allograft valve failure [11,12]. Other studies in humans and animals have demonstrated an increase in donor-specific cytotoxic [13] and helper Tlymphocyte precursors [3]. Using a rat model our group [4] and others [5] have also demonstrated an early and intense cytotoxic T-lymphocyte response along with complete destruction of valve leaflets in allogeneic rats.…”
Section: Discussionmentioning
confidence: 89%
“…Monitoring of donor-reactive immune responses has demonstrated that hyporesponsiveness to the direct pathway can develop shortly after solid organ transplantation and is in general associated with stable graft function (Hornick et al, 1998; De Haan et al, 2000). Donor-specific cytotoxic or T cell hyporesponsiveness has been detected in kidney (Ghobrial et al, 1994; Mason et al, 1996; Mestre et al, 1996; Hornick et al, 1998; Baker et al, 2001b), heart (Hu et al, 1994; Hornick et al, 2000; Van Hoffen et al, 2000) and lung (De Haan et al, 2000) transplantation, although this is not a universal finding (Eberspacher et al, 1994; Loonen et al, 1994; Steinmann et al, 1994; Oei et al, 2000). In addition, hyporesponsivessness to donor antigen presented by the indirect pathway has also been described (Salama et al, 2003b).…”
Section: Donor-specific Treg Control Of Alloimmune Responses Followinmentioning
confidence: 99%